High IL-5 levels possibly contributing to HIV viremia in virologic non-responders at one year after initiation of anti-retroviral therapy. (June 2020) - Shete, Ashwini; Kurle, Swarali; Dhayarkar, Sampada; Patil, Ajit; Kulkarni, Smita; Ghate, Manisha; Sangale, Shashikala; Medhe, Uttam; Rajan, Shobini; Verma, Vinita; Gangakhedkar, Raman
Abstract: Lack of viral monitoring in HIV infected patients on anti-retroviral therapy in low income countries may result in missing virologic non-responders (VNR) who show immunologic recovery in spite of unsuppressed viral replication. Biomarkers and drug resistance patterns in these discordant patients in comparison to the concordant treatment failure group need to be studied to understand possible risk factors associated with this condition. HIV infected patients on anti-retroviral therapy for one year were enrolled under three categories namely VNRs (n = 25), treatment failures (n = 18) and treatment responders (n = 40). They were assessed for HIV drug resistance by sequencing, plasma cytokines by luminex assay, T cell activation status by flow cytometry and total IgE levels by ELISA. VNR and failure patients had significantly lower median baseline CD4 counts than the responders. VNRs had significantly higher CD4 counts but lower viral load than treatment failures at one year of ART. VNRs had the highest eosinophil counts and the highest IL-5 levels among all the groups. IL-5 levels in them correlated with their viral load values. Frequency of Treg cells was also highest among the VNR group participants. More than 60% of the viremic patients irrespective of their groups harboured multiple HIV drug resistance mutations and mutation pattern did not differ between the groups. Low baseline CD4 counts and presence of multiple drug resistance mutations in the viremic groups highlighted the importance of early ART initiation and viral load monitoring irrespective of presence of immunologic failure. High IL-5 levels in VNR group indicated a need for investigating causal relationship between IL-5 and viral replication to devise therapeutic strategies to control viremia. Highlights: Virologic non-responders (VNRs) show immunologic recovery despite virologic failure. VNRs had highest IL-5 levels, frequency of eosinophils and Tregs among all groups. IL-5 levels in VNRs correlated with their viral load values. More than 60% VNRs showed presence of multiple drug resistance mutations. Higher IL-5 levels possibly explain immunologic recovery despite virologic failure.